Clinical and radiographic outcomes using standard length of cannulated screws for traditional Latarjet procedure - Juan M. Lopez-Ovenza, MD; Amaury Tapia, MD; Juan I. Duca, MD (JSES International)
Background: The purpose of this study was to evaluate the clinical and radiographic outcomes of open traditional Latarjet stabilization using 32-mm–long and 30-mm–long cannulated screws in males and females, respectively, with a minimum of 2 years of follow-up. Methods: We retrospectively reviewed open Latarjet procedures using cannulated screws of standard length with a minimum of 2 years of follow-up. Functional evaluation was performed with postoperative Rowe and Walch score, visual analog scale for pain and return to sport. Graft healing was assessed with computed tomography scans at 4 to 6 months postoperatively. Patients were divided into 2 groups according to postoperative radiographic measurements: a bicortical or unicortical screw group. The α angle between the shaft of the screw and the glenoid subchondral bone was measured for superior and inferior screws. Level of significance was 0.05. The post hoc power analysis was 0.89. Results: A total of 69 patients met the criteria for inclusion. Of these patients, 60 (87%) were available for final follow-up (n = 62 shoulders), with a mean age of 28.4 ± 9.5 years (range, 16-55 years) at the time of surgery. Fifty six males (93.3%) and 4 females (6.7%) were included. The mean final follow-up period was a mean of 38 months after the procedure (range, 25-48 months). Eight of 60 patients (13.3%) had persistent apprehension in abduction-external rotation position. One patient (1.7%) had a recurrence of shoulder subluxation. The mean Walch-Duplay score was 90 ± 11.6 points (range, 40-100 points), and the mean Rowe score was 93.4 ± 11 points (range, 50-100 points). The mean visual analog scale score for the evaluation of pain was 0.9 ± 1.3 (range, 0-4). The coracoid healed the glenoid neck in 87.1% (54/62) of the shoulders on the postoperative computed tomography scan. Lower alpha angle for inferior and superior screws had more rate of unicortical fixation (P = .05 and P = .04, respectively). Fourteen of 62 (22.6%) shoulders were found unicortical screws. Six bicortical cases and 2 cases of unicortical screws (25%) showed nonunion (P = .86). There were 2 complications, 1 patient had hematoma that required drainage and 1 case had transient axillary nerve palsy which resolved spontaneously. No complications associated with the hardware were found. Conclusion: Open traditional Latarjet procedure using 32-mm–long and 30-mm–long cannulated screws in males and females, respectively, provided good outcomes with acceptable complication rates. Unicortical screws fixation does not have a higher rate of nonunion than bicortical screws.